Genetics of pediatric central nervous system tumors - Biegel, J A (Journal of pediatric hematology/oncology, 1997)
Pediatric central nervous system (CNS) tumors comprise a wide variety of histologic subtypes ranging from the benign juvenile pilocytic astrocytoma to the highly aggressive atypical teratoid/rhabdoid tumor. Although some brain tumors are seen in association with inherited genetic disorders which predispose to malignancies, most are sporadic. Current knowledge regarding the cytogenetic and molecular genetic events which have been implicated in the development or progression of common brain tumors in children in the subject of this review. Combined cytogenetic and molecular genetic approaches, including fluorescence in situ hybridization, have been used to identify genomic alterations in different histologic types of pediatric brain tumors. The most frequent abnormality in primitive neuroectodermal tumor/medulloblastoma is an i(17q), present in approximately 50% of cases. This finding implicates the presence of a tumor suppressor gene on 17p, which is important in tumor development. A number of genes on 17p have been eliminated as candidates for this locus, including TP53. A tumor suppressor gene in chromosome band 22q11.2 has been hypothesized to play a role in atypical teratoid/rhabdoid tumors, and positional cloning strategies are in progress to identify a rhabdoid tumor gene. Chromosome 22 deletions are also seen in meningiomas and a small percentage of ependymomas, but it is not yet known whether the same gene is responsible for more than one malignancy. With regard to childhood astrocytomas, tumor-associated genetic changes have not yet been identified for the common juvenile pilocytic or low grade diffuse astrocytoma. In contrast, malignant anaplastic astrocytomas and glioblastoma multiforme have abnormalities similar to those seen in adults, including loss of alleles on 17p13 and TP53 mutations, trisomy 7, EGFR rearrangements, and loss of chromosomes 10 and 22. The presence of tumor-associated genetic abnormalities has clinical utility in a differential diagnostic setting, and has lead to the identification of genes which contribute to tumorigenesis.